Enhancing Administrative Efficiency Through the DepEd Caraga Regional Office Information Systems Portal - Pitogo, Nerison S. (International Journal of Computing Sciences Research, 2024)
Purpose – The DepEd Caraga Regional Office Information Systems Portal stands as a modern digital platform, reshaping how administrative processes operate within the regional office. This paper conducts a thorough evaluation of the portal's significant impact, with a strong focus on its main modules. The portal's collection of modules promotes not just operational excellence and smooth workflows but also enables well-informed decision-making. Method – The proponent made use of a descriptive research design that covers both quantitative and qualitative research methods in collecting and analyzing data. Using a sampling technique, the respondents to this study are the regional office personnel of DepEd Caraga region who are the main users of the portal. Results – The study shows that the respondents recognized the existence of the portal as they have been using it every day since its deployment in the office. The document tracking system, ISO portal, and human resource information system topped the most used features that were very useful to the users. Conclusions – Overall, the DepEd Caraga information systems portal provides a satisfactory rating relating to enhancing the office’s administrative efficiency in terms of the portal’s accessibility, usability, work efficiency performance, organization of work, systematization of processes, references of records, and satisfaction with support services, which emphasizes increased collaboration and operational efficiency. Recommendations – The proponent of this study recommends its users to explore the other features of the portal to appreciate more its existence, the ICT unit, to enhance the system by adding more features and integrating information technology into the operational processes for work automation and systematization and encourage other DepEd offices to utilize this initiative given a full support from the management. Practical Implications – The application of information systems is the new trend in every workforce. Information systems provide an ease of doing business through the organization of work and systematized processes.